2005
DOI: 10.1063/1.1871362
|View full text |Cite
|
Sign up to set email alerts
|

Ti gate compatible with atomic-layer-deposited HfO2 for n-type metal-oxide-semiconductor devices

Abstract: The electrical characteristics were evaluated for the metal-oxide-semiconductor (MOS) devices with Ti and Pt gates on the atomic-layer-deposited (ALD) HfO2. The equivalent oxide thickness (EOT) of the Ti gate is shown to be nearly the same as that of the Pt gate, which means that a negligible chemical reaction occurs between the gate and dielectric. The values of the effective metal work function (Φm,eff), extracted from the conventional relations of flatband voltage versus EOT, were ∼4.2eV for Ti and ∼5.4eV f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The metal-work function in vacuum of Ti is 4.33 eV, which is appropriate for NMOS devices. Furthermore, the Fermi-level pinning effect is not significant because the difference between the metal-work function in vacuum and the effective work function of Ti is very small [11]. Post metallization annealing was performed in a reductive gas mixture (10% H 2 and 90% N 2 ) at 400 • C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The metal-work function in vacuum of Ti is 4.33 eV, which is appropriate for NMOS devices. Furthermore, the Fermi-level pinning effect is not significant because the difference between the metal-work function in vacuum and the effective work function of Ti is very small [11]. Post metallization annealing was performed in a reductive gas mixture (10% H 2 and 90% N 2 ) at 400 • C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the EWF may strongly depend on the processing conditions that the device is subjected to [22][23][24][25][26]. For instance, oxygen-rich or oxygen-deficient conditions can result in different interfaces [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our results show that the EWF strongly depends on the type of interfaces, interface roughness and atom substitution content in interfaces, and the EWF of O-Ni interface without defects is as higher as 2.0 eV than that of Hf-Ni interface without defects. For Hf-Ni interfaces, it is found that two calculated effective work functions of interfaces without and with Ni substitution for whole interfacial Hf layer are good for nMOS and pMOS effective work function (EWF) engineering.Farther, one notices that Hf and O vacancies give rise to a considerably large EWF changes25 while Ni vacancy leads to an insensitive change of EWF. In addition, we obtain an expected theoretical relationship that variations of the EWFs are in proportion to that of interface dipole density.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 For high-k based MOSFETs, / ef f of metals has been demonstrated to be strongly dependent on the processing conditions that the device is subjected to. [10][11][12][13][14] It has been reported that / ef f of many metal electrodes shifts toward the middle of the Si band gap upon high temperature annealing, regardless of its vacuum work function. 15 An emerging way to control the relative position of E F (or alternatively, / ef f ) is through the introduction of an interfacial dopant or "capping" layer either at the Si/HfO 2 interface or at the metal/HfO 2 interface.…”
Section: Introductionmentioning
confidence: 99%